Salinity Stress Ameliorates Pigments, Minerals, Polyphenolic Profiles, and Antiradical Capacity in Lalshak - Umakanta Sarker; Md. Nazmul Hossain; Shinya Oba; Sezai Ercisli; Romina Alina Marc; Kirill S. Golokhvast (MDPI AG, 2023)
Previous studies have shown that salinity eustress enhances the nutritional and bioactive compounds and antiradical capacity (ARC) of vegetables and increases the food values for nourishing human diets. Amaranth is a salinity-resistant, rapidly grown C4 leafy vegetable with diverse variability and usage. It has a high possibility to enhance nutritional and bioactive compounds and ARC by the application of salinity eustress. Hence, the present study aimed to evaluate the effects of sodium chloride stress response in a selected Lalshak (A. gangeticus) genotype on minerals, ascorbic acid (AsA), Folin-Ciocalteu reducing capacity, beta-carotene (BC), total flavonoids (TF), pigments, polyphenolic profiles, and ARC. A high-yield, high-ARC genotype (LS6) was grown under conditions of 0, 25, 50, and 100 mM sodium chloride in four replicates following a block design with complete randomization. We recognized nine copious polyphenolic compounds in this accession for the first time. Minerals, Folin-Ciocalteu reducing capacity, AsA, BC, pigments, polyphenolic profiles, and ARC of Lalshak were augmented progressively in the order: 0 < 25 < 50 < 100 mM sodium chloride. At 50 mM and 100 mM salt concentrations, minerals, AsA, Folin-Ciocalteu reducing capacity, BC, TF, pigments, polyphenolic profiles, and ARC of Lalshak were much greater than those of the control. Lalshak could be used as valuable food for human diets as a potent antioxidant. Sodium chloride-enriched Lalshak provided outstanding quality to the final product in terms of minerals, AsA, Folin-Ciocalteu reducing capacity, BC, TF, pigments, polyphenolic profiles, and ARC. We can cultivate it as a promising alternative crop in salinity-prone areas of the world.